Variation Characteristics of Nitrous Oxide Along the East Antarctic Coast - Yongnian Xu; Biao Tian; Jie Tang; Lingen Bian; Minghu Ding; Wanqi Sun; Xiuli Xu; Dongqi Zhang (Journal of Marine Science and Engineering, 2025)
Based on a laboratorial analysis of nitrous oxide (N2O) concentrations collected in gas bottles (glass flask) at the Zhongshan Station on the East Antarctic coast from 2008 to 2021, the variation characteristics and trends in the background concentration of N2O at the station were analyzed and compared with the N2O data from other Antarctic stations. The results showed that the annual average concentration of atmospheric N2O along the East Antarctic coast increased from 320.40 ppb in 2008 to 333.31 ppb in 2021, with an overall increasing trend of 0.99 ppb per year. Pronounced seasonal variability was observed, with elevated concentrations occurring during austral spring–summer and reduced levels in autumn–winter, consistent with the seasonal patterns documented at other Antarctic sites. The overall variation trend of the N2O concentration at Zhongshan Station is basically consistent with the observation results at other stations in Antarctica, suggesting that the station’s background N2O measurements are representative of continental-scale atmospheric composition dynamics. Combined with the analysis of air mass tracks, this seasonal variation in N2O is mainly related to the mass movement of air mass and, to a certain extent, is influenced by the seasonal melting of sea ice and the exchange between the troposphere and stratosphere. The results supplement important basic data on N2O concentrations along the East Antarctic coast and have potential reference significance for further understanding the causes of atmospheric N2O variations in the Antarctic region.